2001
DOI: 10.1016/s0022-5347(05)66130-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Changes in Renal Function After Extracorporeal Shock Wave Lithotripsy in Children

Abstract: Our results demonstrate that shock wave energy induces transient functional damage of tubular function in children. Minimizing the kV. and number of shocks may decrease the deleterious effect. When considering functional regeneration time, the minimal interval between 2 shock wave treatments should be at least 15 days. The long-term effect needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 22 publications
0
23
0
7
Order By: Relevance
“…Secondly, ESWL itself may cause renal injury and result in loss of renal function. Although most clinical studies suggest that the initial decline in GFR is capable of improving with time (20), long-term effects are not known and have yet to be elucidated. Although no significant correlation was observed between the frequency of the ESWL sessions and renal function in the present study, a long-term longitudinal study should be conducted to confirm this point.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, ESWL itself may cause renal injury and result in loss of renal function. Although most clinical studies suggest that the initial decline in GFR is capable of improving with time (20), long-term effects are not known and have yet to be elucidated. Although no significant correlation was observed between the frequency of the ESWL sessions and renal function in the present study, a long-term longitudinal study should be conducted to confirm this point.…”
Section: Discussionmentioning
confidence: 99%
“…Types of SWL machines, shock wave numbers and dosage may have an important role on renal effects. The technical parameters of each SWL machine are different but third generation ultrasound guided machines with a small focal zone is recommended for treating kidney stones in children [15]. The kV and number of shocks are maintained as low as possible and 2 weeks is optimal time to repeat SWL session due to regeneration time of the transient renal proximal tubular dysfunction in children [15].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports confirm that shockwave lithotripsy (SWL) can be performed in children with no suspicion of long-term morbidity of the kidney [19][20][21][22]. Calyceal or renal stones with a stone diameter of up to 2 cm are an ideal indication for ESWL.…”
Section: Conservative Management Of Acute Stone Episodementioning
confidence: 99%
“…Stone-free rates of 67-93 % in short-term and 57-92 % in long-term followup studies have been reported [4,17,18]. Consequently, ESWL can be indicated in children with a larger stone volume, and the placement of a ureteral stent before or after ESWL is generally unnecessary [18,[20][21][22][23][24][25]. The mean number of shock waves for each treatment is about 1,800 and 2,000 (up to 4,000 if needed) and the mean power set varies between 14 and 21 kV.…”
Section: Conservative Management Of Acute Stone Episodementioning
confidence: 99%